PARTITION COEFFICIENTS OF SN(II) AND SN(IV) IN IGNEOUS ROCKS AS RELATED TO THEIR ORE CONTENT - Kovalenko V.I. (My University, 1988)
There have been no experimental or theoretical determinations of the partition coefficients of Sn(II) and SN(IV) in magma systems. In the present article these are estimated by analyzing the partition coefficients of elements similar to SN(II) and SN(IV) in their crystallochemical properties. Various investigators have shown that the partition coefficients of the elements between crystals and melts (K) are strictly related to the ionic radius of the element in each mineral. The ion size of each element in the lattice takes account of its valence, coordination number, spin, and other characteristics of the position of the given element in the mineral lattice. The dependence of the partition coefficients of elements on their ionic radii Ri are shown graphically in the well-known N. Onuma diagrams. Available data indicate that Sn(II) predominates in igneous rocks at the level of their generation, and that Sn(IV) predominates in various igneous minerals, including mantle rocks, at the level where they crystallize. This appears to agree with the experimental estimates of the valence forms in which tin occurs in magmas and their minerals.